Mengapa Kepemimpinan lebih Menentukan daripada Lingkungan Kerja? Bukti Empiris tentang Kualitas Pelayanan Administrasi Desa - Lestari, Riona Raliuw; Johny Urbanus Lesnussa; Selvia F. G. Renyut; Bernard Renyut (Journal of Business Application, 2026)
This study examines the influence of village head leadership and the work environment on administrative service quality in Souhuwe Village, West Seram Regency, Indonesia. Improving administrative services at the village level remains a challenge, particularly in areas with limited organizational capacity and public service resources. This study employed a quantitative explanatory research design using multiple linear regression analysis. Data were collected from 43 respondents consisting of village officials and community members who received administrative services during the research period. Data analysis was conducted through validity and reliability tests, classical assumption tests, and hypothesis testing using SPSS. The findings reveal that village head leadership has a positive and significant influence on administrative service quality, indicating that effective leadership plays an important role in directing, coordinating, and motivating village officials to improve service performance. Meanwhile, the work environment does not show a significant partial influence on administrative service quality. However, both variables simultaneously contribute to explaining variations in administrative service quality. These findings highlight that strengthening leadership capacity is a key strategy for improving village administrative services, while organizational conditions remain an important supporting factor in achieving effective local governance.